Keefektifan Konseling Kelompok Behavioral Teknik Self Management untuk Mereduksi Kecanduan Media Sosial Aplikasi Tik-Tok Pada Siswa SMP - Andrian Andrian; Leny Latifah; Eva Kartika Wulan Sari (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2026)
Currently, technology is developing so rapidly, this also has an impact on the development of information as evidenced by the increasingly sophisticated means of human communication. Social media is one manifestation of this development, for example the increasingly widespread use of TikTok as a communication medium. Indicators of someone who is addicted to this facility are shown by people's lifestyle experiencing drastic changes, health being neglected, family and friends being ignored, and neglect of personal obligations. The study conducted by researchers aims to analyze whether the use of behavioral group counseling with self-management techniques is effective in reducing students' TikTok social media addiction. The study was carried out experimentally in the form of a one group pre-test and post-test using seven students as samples. In the process, researchers used purposive sampling. During the research process, scale instruments related to research variables were used to achieve research objectives. Data analysis in the author's study shows that there is a difference between the level of addiction to this social media application during the pre and post-test. As a result, the conclusion is that behavioral group counseling, self-management techniques to reduce addiction to the social media application TikTok in junior high school students, is effective. Apart from that, there is a difference in the mean of the two test results which shows that the post-test mean is 86 while the pre-test mean is 36. The researchers' findings in this study were the existence of student responsibility, student commitment, student openness, intimate with family, and seeking of activity. The conclusion of the results of this research shows that providing group counseling with self-management techniques is effective in reducing addiction to the social media application Tik-Tok. Suggestions for future researchers are that this research should not stop at just being reported but can result in the publication of the research results.